The effect of culturally appropriate self-care intervention on health literacy, health-related quality of life and glycemic control in Iranian patients with type 2 diabetes: A controlled randomized clinical trial - Behnaz Amoozadeh; Akram Parandeh; Feryal Khamseh; Mohammad Ali Sheikh Beig Goharrizi (Wolters Kluwer Medknow Publications, 2023)
Background: Cultural and language differences are necessary factors for diabetes management and self-care education programs in patients suffering from diabetes. This study aims to investigate the effectiveness of culture-based self-care intervention on health literacy, quality of life, and glycemic parameters in patients with type 2 diabetes. Materials and Methods: This randomized clinical trial has been carried out in selected centers in Darreh Shahr, Iran; 80 participants were randomly assigned into intervention and control groups. The intervention group received an educational program for 6 sessions twice a week, but the control group only received routine services. Data were collected using health literacy and life quality scales for diabetic patients, which were completed by both groups before, immediately after, and 3 months after the intervention; hemoglobin A1C (HbA1c) was checked before and 3 months after the intervention. SPSS software was also analyzed data using χ2, Fisher's exact, independent t, and repeated measures analysis of variance tests. Results: There were no significant differences between the 2 groups before the study (p >0.05) goes forward. But, mean scores of health literacy (F2,40 = 5.61, p =0.007), quality of life (F2, 40 = 4.09, p =0.01), and HbA1c levels (t, 39 = 6. 91, p <0.001) have shown significant differences between the 2 groups immediately and 3 months after the intervention have been applied. Conclusions: Culturally appropriate intervention should be offered as a part of the nurse' care program for diabetic to control HbA1c, and improve their life quality and health literacy.